The Experience of Adults Bereaved by the Suicide of a Close Elderly Relative: A Qualitative Pilot Study - Michaud-Dumont, Gabrielle; Lapierre, Sylvie; Viau-Quesnel, Charles (Frontiers in Psychology, 2020)
Suicide in older persons is a serious issue in many countries. The act of intentionally causing one’s own death is often associated with lack of social support, thwarted belongingness, or chronic interpersonal difficulties. Therefore, suicide has a significant interpersonal dimension that can influence those left behind. However, studies that have investigated the impact of older adults’ suicide on their family are scarce. The objective of this pilot study was to assess the feasibility of a qualitative research on the psychosocial experience of adults bereaved by the suicide of an elderly relative. This research could recruit three participants (daughter, grand-son, and grand-niece) who had lost to suicide a close family member aged between 75 and 90. The analysis of the content of the semi-structured interviews revealed seven main themes: (1) finding an explanation to the suicide, (2) give meaning to the loss, (3) the emotional processes of mourning, (4) the repercussions of the suicide on the individual and the family, (5) looking for support, (6) the taboo and secrecy of suicide, and (7) perceptions of aging and the end of life. To explain the suicide of their loved one, the bereaved mentioned various factors related to aging, such as loss of autonomy, illness, and fear of placement. Although the older relative was perceived to be approaching death because of his/her age, the suicide was still unexpected and shocking and led to various emotions (shock, anger, and guilt) and to family conflicts. Suicide remains a taboo subject, but the newly legalized medical assistance in dying is seen as a potential solution to suffering in old age. Further investigation is clearly needed on this topic and this pilot study indicates that the main difficulties will lie in the choice of selection criteria for participants and in the recruitment process.